2018
DOI: 10.21500/20112084.3332
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between sensation seeking and risky alcohol drinking in Mexican adolescents: An structural modeling equation approach.

Abstract: Alcohol drinking represents one of the most important public health problems in adolescents. One axis of analysis of the correlates that affect alcohol consumption in adolescents is personality traits. In particular, sensation seeking maintains a consistent relationship with consumer behaviors. The objective of this research was tested in a structural equation model to show the structural effect of sensation seeking on risky alcohol drinking. The sensation seeking inventory (Palacios, 2015a) was used and alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
(70 reference statements)
0
1
0
6
Order By: Relevance
“…La estructura final coincide con la estructura original de la escala (OMS, 2011) y se trata de un instrumento con contenidos culturalmente relevantes, dado el proceso de adaptación que se siguió (OMS, 2020). Los resultados encontrados coinciden con lo propuesto por Palacios (2018), que señala que los diferentes aspectos del consumo pueden agruparse en un indicador coherente.…”
Section: Discusión Y Conclusionesunclassified
See 2 more Smart Citations
“…La estructura final coincide con la estructura original de la escala (OMS, 2011) y se trata de un instrumento con contenidos culturalmente relevantes, dado el proceso de adaptación que se siguió (OMS, 2020). Los resultados encontrados coinciden con lo propuesto por Palacios (2018), que señala que los diferentes aspectos del consumo pueden agruparse en un indicador coherente.…”
Section: Discusión Y Conclusionesunclassified
“…Constituye el periodo de transición entre la infancia y la adultez, entre los 10 y 19 años aproximadamente; durante este tiempo se suelen experimentar crisis, conflictos y contradicciones en la búsqueda de una mayor independencia psicológica y social (Gutiérrez et al, 2016). Los cambios propios de esta etapa, sumados a las condiciones del ambiente y a las presiones sociales, los hace vulnerables al consumo de sustancias (Palacios, 2018) lo que en muchos casos resulta en un fenómeno normativo propio de la exploración del ambiente en dicha etapa del desarrollo.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…En la población estudiantil, especialmente la universitaria, se han referido prevalencias de consumo de alcohol preocupantes, especialmente en los hombres, tanto en países anglosajones y europeos (Davoren et al, 2016;Hamilton et al, 2020;Saether et al, 2019), como en Iberoamérica (Betancourth et al, 2017;Cortés et al, 2014;Ministerio de Salud, 2018). De este modo, aunque en estudios recientes se encuentran datos esperanzadores respecto a la reducción del consumo perjudicial de alcohol en adultos jóvenes (18 a 24 años), también se reconocen los importantes efectos adversos que tiene este tipo de consumo en la salud, así como en el funcionamiento psicosocial de este sector de la población (Visontay et al, 2020), constatándose el valor predictor de la búsqueda de sensaciones en los consumos problemáticos (Palacios, 2018).…”
Section: Alcohol Consumption Patterns and Perception Of Risk In Mexicunclassified
“…Adolescences who have higher personal resiliency (a component of psychological capital) report less frequent risk behaviors (Prince-Embury, 2015). Previous studies revealed that several individual factors have been confirmed in predicting high-risk behaviors in adolescents (Chen et al, 2006;Claro et al, 2015;Lipowski et al, 2016;Palacios, 2018;Safa et al, 2020;Zuckerman, 2007a). Accordingly, the present study aimed to explain the group membership model of high school students with high-risk behaviors based on individual indicators.…”
Section: Introductionmentioning
confidence: 99%